Temperature‐Driven Perturbations in Growth Kinetics, Structural and Optical Properties of NiO Thin Films. Issue 21 (24th September 2021) - Mishra, Monu; Barthwal, Swapnil; Tak, Bhera Ram; Singh, Rajendra
Abstract : Nickel (II) oxide (NiO) is an emerging transparent semiconducting oxide with potential applications in modern‐world ultraviolet active solar cells and visible‐blind photodetectors. Despite their critical importance, the synthesis of quality NiO thin films has remained a challenging issue. Therefore, herein, an analysis of the temperature‐driven perturbations in the growth kinetics of associated properties of NiO thin films grown via radio‐frequency sputtering technique is reported. The structural, morphological, and optical properties of NiO films grown at various temperatures are probed and the obtained results are correlated thoroughly. It is observed that variation in growth temperature (30−500 °C) alters the growth mechanism (from Volmer–Weber to Stranski–Krastanov), surface features, stoichiometry, crystallite size, stress/strain, as well as dislocation densities. The increment in Urbach energy at elevated temperatures indicates that the thermal excitation induces high adatom mobility, leading to poor crystallinity and high disorder. Interestingly, it is witnessed that NiO films' growth at temperatures >300 °C exhibits stress relaxation via generation of higher defect states, lower surface roughness due to increased adatom mobility, and the suppression of first‐order Raman vibrational states (one‐phonon longitudinal optical [1PLO] mode) associated with Ni vacancies. Hence, it is concluded that NiO films grown at 200 and 300 °C possess superior material properties, that is, largest crystallite size (≈20 nm), lower defects, and high transmittance (>90%) for device‐related applications. Abstract : Herein, temperature‐driven perturbations in the growth kinetics and structural, morphological, and optical properties of NiO thin films grown at different substrate temperatures (i.e., 30–500 °C) via radio‐frequency sputtering technique are reported. Temperature‐induced thermal excitation and adatom mobility lead to significant modifications in crystallite size, defect density, stress relaxation, and the optical bandgap of the grown films.